The Impact of Knowledge Management Systems in Enhancing the Competitiveness of Retail Companies - Muttaqi, Fajar; Zogara, Lukas Umbu; Alfaujianto, Moh.; Surahmat, Asep (Scientific Journal of Information System, 2025)
This study investigates the role of Knowledge Management System (KMS) implementation inenhancing the competitiveness of retail companies, with a specific focus on Lotte Mart Indonesia.Using a qualitative exploratory case study approach, the research collected data through in-depthinterviews, field observations, and company document analysis. The findings demonstrate that KMSaccelerates the flow of information, reduces duplication, and improves operational efficiency, therebyenabling better coordination among departments. Furthermore, KMS facilitates knowledge sharingand collaboration, which supports the development of service innovations and responsive marketingstrategies. Employees reported that the system allows faster access to documents, real-time inventorychecking, and more structured workflows. Beyond operational benefits, KMS contributes tostrengthening customer satisfaction through improved responsiveness and accurate informationdelivery. Additionally, KMS supports the company’s digital transformation by integrating internalsystems such as ERP, CRM, and e-commerce platforms. Overall, KMS functions not only as aknowledge repository but as a strategic enabler of sustainable competitive advantage in the retailsector.